Predictors of prodromal Parkinson’s disease in young adult Pink1−/− rats - Lechner, Sarah A.; Welsch, Jacob M.; Pahapill, Natalie K.; Kaldenberg, Taylor A. R.; Regenbaum, Amy; Kelm-Nelson, Cynthia A. (Frontiers in Behavioral Neuroscience, 2022)
Parkinson’s disease (PD) is a progressive, degenerative disease that affects nearly 10 million people worldwide. Hallmark limb motor signs and dopamine depletion have been well studied; however, few studies evaluating early stage, prodromal biology exist. Pink1−/− rats, a rodent model of PD mitochondrial dysfunction, exhibit early stage behavioral deficits, including vocal communication and anxiety, that progress during mid-to-late adulthood (6–12 months of age). Yet, the biological pathways and mechanisms that lead to prodromal dysfunction are not well understood. This study investigated the Pink1−/− rat in young adulthood (2 months of age). Mixed sex groups of Pink1−/− rats and wildtype (WT) controls were assayed for limb motor, anxiety, and vocal motor behaviors. A customized NanoString CodeSet, based on genetic work in later adulthood, was used to probe for the up regulation of genes involved in disease pathways and inflammation within the brainstem and vocal fold muscle. In summary, the data show sex- and genotype-differences in limb motor, anxiety, and vocal motor behaviors. Specifically, female Pink1−/− rats demonstrate less anxiety-like behavior compared to male Pink1−/− rats and female rats show increased locomotor activity compared to male rats. Pink1−/− rats also demonstrate prodromal ultrasonic vocalization dysfunction across all acoustic parameters and sex differences were present for intensity (loudness) and peak frequency. These data demonstrate a difference in phenotype in the Pink1−/− model. Tuba1c transcript level was identified as a key marker negatively correlated to ultrasonic vocalization at 2 months of age. Identifying genes, such as Tuba1c, may help determine early predictors of PD pathology in the Pink1−/− rat and serve as targets for future drug therapy studies.